A Zn based coordination polymer exhibiting long-lasting phosphorescence. Issue 56 (14th June 2016) - Cepeda, Javier; Sebastian, Eider San; Padro, Daniel; Rodríguez-Diéguez, Antonio; García, Jose A.; Ugalde, Jesus M.; Seco, Jose M.
Abstract : A coordination polymer consisting of Zn and 6-aminoisonicotinate shows an initial bright blue fluorescence that turns into persistent green phosphorescence. Abstract : A new Zn(ii ) based coordination polymer (CP) built by the cohesive pilling of 2D Shubnikov type layers is reported. This material exhibits time dependent multicoloured emission, part of which shows a persistent green phosphorescence visible for up to two seconds to the naked eye, which originates from multiple charge transfer mechanisms.